Heberferón®’s economic feasibility in patients with high-grade brain tumors without therapeutic options - María Margarita Ríos Cabrera; Iraldo Bello Rivero; Javier Cruz Rodríguez (Medisur)
Foundation: neoplastic diseases in general and particularly those of the central nervous system constitute health problems that negatively impact personal, family and society life. Therefore, the search for new therapeutic modalities that produce an impact on survival and economic feasibility in their use is very important. Objective: to demonstrate the economic feasibility of the interferons (Heberferón®) combination compared to other products approved or under study in the national and foreign contexts in the patients treatment with high-grade brain tumors without therapeutic options. Methods: a cost-effectiveness economic evaluation was developed in a 40 patients sample (23 treated with Heberferón® and 17 with Nimotuzumab) treated at the Arnaldo Milián Castro Santa Clara Provincial Hospital. The effectiveness parameter for each of the comparators was obtained by doing a systematic search in Medline (Pubmed) and Cochrane. Results: Heberferón® was less expensive for each month of life saved in relation to the rest of the medications. Conclusions: the economic feasibility of using Heberferón® was evident, when comparing it with other products to treat patients with highly malignant brain tumors without therapeutic options.